Ta có:
\(\begin{array}{l}\left( {\frac{{\sqrt {22} - \sqrt {11} }}{{1 - \sqrt 2 }} + \frac{{\sqrt {21} - \sqrt 7 }}{{1 - \sqrt 3 }}} \right)\left( {\sqrt 7 - \sqrt {11} } \right)\\ = \left( {\frac{{\sqrt {11} \left( {\sqrt 2 - 1} \right)}}{{ - \left( {\sqrt 2 - 1} \right)}} + \frac{{\sqrt 7 \left( {\sqrt 3 - 1} \right)}}{{ - \left( {\sqrt 3 - 1} \right)}}} \right)\left( {\sqrt 7 - \sqrt {11} } \right)\end{array}\)
\(\begin{array}{l} = \left( { - \sqrt {11} - \sqrt 7 } \right)\left( {\sqrt 7 - \sqrt {11} } \right)\\ = - \left( {\sqrt 7 + \sqrt {11} } \right)\left( {\sqrt 7 - \sqrt {11} } \right)\\ = - \left( {7 - 11} \right) = - \left( -4 \right) = 4\end{array}\)